Patient Satisfaction with Dental and Oral Health Services: A Cross-Sectional Study at Universitas Syiah Kuala Dental Hospital - Andriany, Poppy; Novita, Cut Fera; Mulkhairul, Ilham; Rahmayani, Liana; Sofya, Pocut Aya; Ilham, Mohd (Journal of Syiah Kuala Dentistry Society, 2025)
Background: Patient satisfaction refers to the degree of positive feelings experienced by patients as a result of the healthcare services received, particularly when these services meet or exceed their expectations. Assessing patient satisfaction is essential for evaluating the quality of healthcare services, including dental and oral care. Objective: This study aimed to assess the level of patient satisfaction with dental and oral health services at Universitas Syiah Kuala Dental Hospital. Methods: A descriptive study with a cross-sectional design was conducted from September to October 2024. A total of 100 patients who had completed treatment at Universitas Syiah Kuala Dental Hospital were selected using purposive sampling. Data were collected through a structured questionnaire based on five dimensions of service quality: responsiveness, tangibles, reliability, assurance, and empathy. Results: The results showed a high level of patient satisfaction across all dimensions: responsiveness (97%), tangibles (88%), reliability (99%), assurance (98%), and empathy (99%). Conclusion: The overall level of patient satisfaction with dental and oral health services at Universitas Syiah Kuala Dental Hospital was found to be high, indicating that the hospital provides quality services aligned with patient expectations.